Antitumoral, mutagenic and (anti)estrogenic activities of tingenone and pristimerin - Gomes, Juliana P. M. [UNESP]; Cardoso, Cassia R. P. [UNESP]; Varanda, Eliana Aparecida [UNESP]; Molina, Jose-Manuel; Fernandez, Mariana F.; Olea, Nicolas; Carlos, Iracilda Zeppone [UNESP]; Vilegas, Wagner [UNESP] (Soc Brasileira Farmacognosia, 2011)
Cancer constitutes the second main mortality cause in the world, after cardiovascular diseases. In spite of the progresses in the chemotherapeutics treatments, many patients fail chemotherapy, mainly because of side effects or multi-drugs resistance, proving the need and importance of the research for new molecules with anticancer activity, more effective and with smaller adverse effects. Various compounds derived from plant secondary metabolites are commonly used in the chemotherapy against cancer and the natural products play an important role in the research for new molecules. Among several molecules of natural origin evaluated by MTT assay in murine tumor cell lines [breast (LM3) and lung (LP07)] the quinona-methide triterpenes tingenone and pristimerin showed marked cytotoxic activity presenting IC50 around 2 and 5 mu M respectively. The structure-activity relationship suggests that rings A and B containing an alpha, beta-unsaturated carbonyl group are essential for the observed cytotoxic activity. The interaction between these positions and acetylcisteyne residues suggests a probable mechanism of action. The in vitro mutagenic activity was also evaluated by the Salmonella microsome assay (Ames test) for pristimerin and tingenone with and without metabolic activation (S9) in the strains TA98, TA97a, TA100 and TA102, none of which showed mutagenic potential in any strains. Estrogenic and anti-estrogenic activities were also studied by the e-screen assay in MCF-7 cells with negative results. The present data point to the importance of pristimerin and tingenone as representative of an emerging class of potential anticancer chemicals.
Keywords: (anti)estrogenic activity; cytotoxic activity; mutagenic activity; plumericin; pristimerin; tingenone